Synergistic Sealing of the Pleural Space: Combining Thoracoscopic Talc Poudrage and IPC for Malignant Pleural Effusion—A Case Series - Mas Fazlin Mohamad Jailaini; Azat Azrai Azmel; Mohd Zulkifli Mohd Zain; Mohamed Faisal Abdul Hamid (Respirology Case Reports, 2025)
ABSTRACT Management of malignant pleural effusion (MPE) via medical thoracoscopy presents a clinical challenge, particularly when deciding whether to proceed with talc poudrage during the same setting. This decision is often complicated by uncertainty about lung re‐expansion and the potential failure of pleurodesis. We describe a series of three patients with cancer‐associated MPE who underwent medical thoracoscopy with talc poudrage combined with indwelling pleural catheter (IPC) insertion. This combined approach served as a practical and effective strategy, offering immediate symptom relief, facilitating early pleural symphysis when feasible, and providing a reliable fallback option in cases of non‐expanding lung. The dual‐modality technique highlights a safe, flexible pathway for managing MPE with improved procedural confidence and patient‐centred outcomes. We report 3 cases of MPE successfully achieving pleurodesis with a combination of talc poudrage and IPC, resulting in removal of IPC on follow‐up.